The astrometric observing campaign for the first interstellar object, `Oumuamua - Meech, K. J. (2025)
The first interstellar object, lI/‘Oumuamua, was discovered by the Pan STARRS telescope on 2017 Oct. 19, with 4 images obtained in poor seeing conditions. Pre-recovery data from 18 Oct. gave equally good fits to an ellip tical or parabolic orbit. Additional observations up through 22 Oct. showed that the object had a hyperbolic orbit [1], II was moving very fast when it was discovered, and many objects like this can be lost without immedi ate follow up. In addition to physical and compositional studies our team continued to image ‘Oumuamua to constrain its trajectory with astromet ric measurements, with the last observations made on 2018 Jan. 2, when it was fainter than V ~ 27 mag at a heliocentric distance of 2.9 au with the Hubble Space Telescope.